Comparison of multi-temporal polarimetric airsar data for vegetation mapping : a case study in Cameron Highlands [electronic resource] - 493508 Azian Mohd. Nordin (2010)
Project Paper (Sarjana Muda Sains (Remote Sensing)) - Universiti Teknologi Malaysia, 2010